STUDENTS’ ANXIETY WHILE READING ALOUD DURING ENGLISH LEARNING IN THE ELEVENTH GRADE OF MAN 2 LAMONGAN - Amiatun Nuryana; Lukman Fahmi (IKIP Widya Darma, 2024)
The objectives of this study are to find out the factors causing students’ anxiety while reading aloud during English learning in the eleventh grade of MAN 2 Lamongan and to find out the teacher’s strategies to overcome the problems of students’ anxiety while reading aloud during English learning at the eleventh grade of MAN 2 Lamongan. This study uses a qualitative method. The subjects in this study were class 11 of MAN 2 Lamongan. Data was collected by using interviews and observation to determine the factors causing students’ anxiety. The results of observation showed that the biggest factor causing students’ anxiety was fear of making mistakes. Based on interviews, various factors cause students’ anxiety while reading aloud during English learning. There are at least five factors found in this study, namely, they feel that reading aloud in English learning is difficult, shyness and lack of confidence, fear of making mistakes, fear of being laughed at or mocked by their friends or classmates, and lack of vocabulary. Whereas the result that the teacher’s strategies to overcome the problems of students’ anxiety while reading aloud during English learning are various strategies, there are: preparation, positive thinking, building a good atmosphere while learning, peer groups, and using games method while learning.